Improving Suicide Prevention in Primary Care for Differing Levels of Behavioral Health Integration: A Review - Spottswood, Margaret; Lim, Christopher T.; Davydow, Dimitry; Huang, Hsiang (Frontiers in Medicine, 2022)
Importance: Suicide prevention implementation in primary care is needed due to the increasing rate of suicide in the past few decades, particularly for young and marginalized people. Primary care is the most likely point of contact for suicidal patients in the healthcare system. Attention to the level of medical integration with behavioral health is vital to suicide prevention and is applied throughout this review. Methods: A narrative review was performed. Observations: Many interventions help improve suicide prevention care. PCP education, screening, safety planning/lethal means reduction, care transitions, psychotherapy, and medication management are all evidence-based strategies. Additionally, the pragmatic topics of financing suicide prevention, supporting providers, enacting suicide postvention, and preparing for future directions in the field at each level of primary care/behavioral health integration are discussed. Conclusions and relevance: The findings are clinically relevant for practices interested in implementing evidence-based suicide prevention strategies by attending to the behavioral health/medical interface. Leveraging the patient/provider relationship to allow for optimal suicide prevention care requires clinics to structure provider time to allow for emotionally present care. Defining clear roles for staff and giving attention to provider wellbeing are also critical factors to supporting primary care-based suicide prevention efforts.